Efficacy of a commercial glutaraldehyde footbath product for the control of bovine digital dermatitis - Krömker, Volker; Paduch, Jan-Hendrik; Grabowski, Nils Th.; Seeth, Martin tho (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2018)
Objective: To evaluate the relative efficacy of a novel, commercially available disinfecting agent containing ≥ 15 to < 20 % glutaraldehyde in a hydro-colloid matrix (“EIMÜ Klauen Sprint®”; Eimermacher, Nordwalde, Germany, Biozid-Desinfektionsmittel, BAuA Nr. N-57213) as a walkthrough footbath in order to treat digital dermatitis of dairy cattle. Material and methods: The study was conducted in a dairy farm located in northern Germany from June 1st, 2015 to September 5th, 2015. Eighty-eight cows were enrolled in this study. In both trials of the study, a walkthrough footbath was applied on five consecutive milking times per week. Trial 1 was a blinded, randomised and controlled intervention study. The therapy group (n = 40) received the novel glutaraldehyde product in a 2 % solution while the control group (n = 40) was led through a footbath containing pure water. Trial 2 was a longitudinal study to investigate the development of claw health over a longer time period regarding the use of the new footbath solution. In trial 2 the disinfecting footbath was applied to all trial cows (therapy and control group) of trial 1. The development of claw health and lameness was systematically monitored in the two groups on days 0, 9, 17, 29, 35 (trial 1) and days 42, 68, 94 (trial 2), respectively. The adjusted odds of digital dermatitis lesions (DDL) throughout the study were analysed by mixed logistic regression models. Results: The odds of DDL were 0.15 for the glutaraldehyde foot-bath group compared to the control group. Hence, the disinfecting footbath significantly reduced the DDL prevalence and increased the cure rate of DDL. However, no preventive effect on new digital dermatitis (DD) cases could be identified. Conclusion: The efficacy of the novel glutaraldehyde footbath was evaluated and it was concluded that “EIMÜ Klauen Sprint®” was well tolerated over a longer period of time and might therefore be an effective tool to control DD. Clinical relevance: In future, „EIMÜ Klauen Sprint®“ could be used within a Mortellaro sanitation concept and thereby might help to solve a major problem of dairy cattle farms.
Keywords: Claw health; lameness; herd therapy; disinfecting footbath